Landscape-Scale Long-Term Drought Prevalence Mapping for Small Municipalities Adaptation, the Czech Republic Case Study - Floková, Ludmila; Mikita, Tomáš (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2023)
Drought is a phenomenon that is strengthening with the progress of climate change. Many fields of human activities such as agriculture, forestry, ecology, economy, water supply, or energy production are affected. Municipalities are one of the most important actors, because final adaptation often takes place at this level. However, planning measures is challenging for small municipalities, with adaptation capacity being lower than in big cities. A model working with data from the Global Change research Institute CzechGlobe and the Czech national drought monitor Intersucho allows for information to be obtained at the landscape scale about drought, and their utilization for small municipalities is introduced. In addition to detailed maps for the years 1991-2014, the model enables long-term prediction of drought prevalence for the years 2021-2040 and 2041-2060. GIS-integrated Random Forest regression and twelve climate, topography, and land use/land cover variables were involved in the model construction. The tuned model could explain 70% of reference data variability, and was used for drought prevalence mapping in 20 m spatial detail. Utilisation of overlay and visualisation tools and consultation of actual spatial planning maps helped create maps for spatial decision-making support in precautionary measure and landscape management within the municipalities.
Keywords: drought modelling; Random Forest; municipalities; adaptation; bivariate map; Czech Republic